Physics-Based Modeling and Experimental Study of Si-Doped InAs/GaAs Quantum Dot Solar Cells - A. P. Cédola; D. Kim; A. Tibaldi; M. Tang; A. Khalili; J. Wu; H. Liu; F. Cappelluti (International Journal of Photoenergy)
This paper presents an experimental and theoretical study on the impact of doping and recombination mechanisms on quantum dot solar cells based on the InAs/GaAs system. Numerical simulations are built on a hybrid approach that includes the quantum features of the charge transfer processes between the nanostructured material and the bulk host material in a classical transport model of the macroscopic continuum. This allows gaining a detailed understanding of the several physical mechanisms affecting the photovoltaic conversion efficiency and provides a quantitatively accurate picture of real devices at a reasonable computational cost. Experimental results demonstrate that QD doping provides a remarkable increase of the solar cell open-circuit voltage, which is explained by the numerical simulations as the result of reduced recombination loss through quantum dots and defects.